Improving English Learning by Gamification with MDA Framework - Frieska Angelia; Suharjito Suharjito; Sani Muhamad Isa (Journal of Games, Game Art, and Gamification, 2020)
Information technology is proliferating and drives the learning process toward e-learning. At the moment, people can learn from their gadget through learning sites, applications, or games. However, to improve users’ motivation, e-learning must be appealing. Researchers have introduced the concept of gamification to make learning more entertaining. The primary purpose of this research is to understand how the proposed gamification elements using Mechanics, Dynamics, and Aesthetics (MDA) framework improve users' motivation and learning outcomes in English learning. For this research, we use 6-11 framework defining six aspects of emotion and eleven aspects of instinct. We collected users’ scores then analyzed them by using a t-test. We also used a questionnaire to access the users' experience. The results suggest that most of the respondents are motivated to learn more deeply. We conclude that the proposed gamification elements improve users' motivation and learning outcomes.